The Applications of Machine Learning in Education Science Research - Son, Nguyen Thi Kim; Huong, Bui Thi Thanh; Tho, Chu Cam; Anh, Pham Tuan; Tri, Nguyen Quoc (VNU Journal of Science: Education Research; Vol 37 No 4DO - 10.25073/2588-1159/vnuer.4562, 2021)
The article presents an overview of the application of machine learning techniques in education science research. The research process shows the use of technology in learning and teaching, collecting information, analyzing and processing data to provide high-accuracy answers or advice in solving educational issues is the trend and strength in education science research. Through this, the authors make recommendations on some research directions in the field of education approaching international publications.